Spatial analysis of landslide vulnerability in Enrekang District, South Sulawesi. Issue 1 (April 2020) - Ahmad, A; Lopulisa, C; Imran, A M; Baja, S; Solle, M S
Abstract: Enrekang is one of the districts in South Sulawesi, which including prone areas to landslides disaster in Indonesia. Landslide events are strongly influenced by trigger factors, namely; climate, earthquakes and human activities in utilising land, while geological factors, soil factors, hydrogeological factors, land use factors and geomorphological factors (slopes and landforms) are the controlling factors for the occurrence of landslides. This study aims to link the controlling factors and triggering factors to delineate the level of landslide vulnerability in Enrekang Districts to become more detailed. The method used is the scoring with Analytical Hierarchy Process (AHP) method. The parameters were; slope, geology (lithology and structure), land cover, landform, population map, rainfall, texture of soil and earthquake event. This parameter will be evaluated by several experts through a questionnaire. The expert assessment results will be analysed further with expert choice software to get the weight values of each parameter. The weight obtained will be used to assess the vulnerability of landslides by using Argis 10.3 software by overlaying each parameter. The vulnerability of Enrekang districts is divided into five, namely very low vulnerability (1%), low (5%), moderate (21%), high (51%), and very high (22%). The Areas with a very high level of vulnerability can be found in the northern part of Maiwa Sub-District, most Enrekang Sub-Districts, the northern part of Buntu Batu Sub-District, the west to the north of Alla subdistrict, and the northern and eastern parts of Curio sub-district, and the southern part of Baraka Sub-District. Most of Enrekang Districts has a high vulnerability of landslide, so the application of vegetative and mechanical soil conservation techniques is needed in utilising land in sloping areas to prevent landslides.